Anisotropy of strength and plasticity in single-colony lamellar structure of Ti‒6Al‒4V alloy. (1st March 2020) - Mine, Yoji; Matsuzaki, Yuya; Takashima, Kazuki
Abstract: Micro-tensile tests were performed on single-colony specimens to elucidate the anisotropic slip behaviour in Ti‒6Al‒4 V alloy with a lamellar microstructure. The critical resolved shear stress (CRSS) of 〈 c + a 〉 pyramidal slip was more than 1.5 times higher than that of 〈 a 〉 slip. The CRSSes of 〈 a 〉 slips increased with increasing length fraction of β phase along the slip direction, revealing that the β phase acts as a hard phase for soft orientations. The 〈 c + a 〉 pyramidal slip with β laths exhibited a low CRSS value compared with that of a Ti–5Al solid solution, suggesting that the β phase facilitates the 〈 c + a 〉 slip. Graphical abstract: Image, graphical abstract